Narrative Testimony as Theoretical Method: Examining the Critical Debate on the Culture of Policing Homosexuality in the Jamaican Context: Наративното сведоштво како теориски метод: Испитување на критичката дебата за културата на надзор врз хомосексуалноста во јамајкански контекст - Cummings, Ronald; Janeva, Kalina (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Ronald Cummings | Роналд Камингс Title (English): Narrative Testimony as Theoretical Method: Examining the Critical Debate on the Culture of Policing Homosexuality in the Jamaican Context Title (Macedonian): Наративното сведоштво како теориски метод: Испитување на критичката дебата за културата на надзор врз хомосексуалноста во јамајкански контекст Translated by (English to Macedonian): Kalina Janeva | Калина Јанева Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 177-199 Page Count: 20 Citation (English): Ronald Cummings, “Narrative Testimony as Theoretical Method: Examining the Critical Debate on the Culture of Policing Homosexuality in the Jamaican Context,” Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008): 177-199. Citation (Macedonian): Роналд Камингс, „Наративното сведоштво како теориски метод: Испитување на критичката дебата за културата на надзор врз хомосексуалноста во јамајкански контекст“, превод од англиски Калина Јанева, Идентитети: списание за политика, род и култура, т. 6, бр. 2-3 (лето 2007 - зима 2008): 177-199.